Implikasi Postfeminisme Terhadap Degradasi Moral Bangsa - H. Abd. Muis Said (AN-NISA, 2018)
Post-feminist discourse whose features are almost the same as postmodernist theory make life style also influenced. Consumerism, hedonism, as well as various doctrines of feminism that are not in line with the concept of religion, will result in the dilapidation of one's behavior. What's worse is when women are always isolated from their functions and roles. Therefore, women must come out of a humble stigma that has already been constructed in the community and motivates from and their people so that they do not participate in the paradigm of thinking of postfeminism which leads to dichotomy.